Ornament as portable ecology: Bodily and architectural adornment on a global scale - Papapetros, Spyros (Interstices: Journal of Architecture and Related Arts, 2017)
2017 Interstices Under Construction Symposium: Pattern / Surface a pursuit of material narratives. 2nd - 4th June, Auckland University of Technology.